The study of defamation among academicians in UiTM, Kota Samarahan Campus / Mohd Rafiz Salji ... [et al.] - Salji, Mohd Rafiz; Sa' Ari, Haziah; Idrus, Marlia (2010)
People communicate with each other using a variety of mediums. However, there are far greater risks of miscommunication and defamatory statements. Objective of this research was to study the academician's opinion in rglation to defamation In their workplace. Academicians in UiTM, Kota Samarahan campus have answered a questionnaire regarding existence, effects and causes of defamation. Recommendation to avoid defamation was also been studied. As result, there was no proving of defamation's existence in workplace. It also supported by negative results analysis on existence's identification of defamation.